"I got tested at home, the help came to me": acceptability and feasibility of home‐based TB testing of household contacts using portable molecular diagnostics in South Africa. Issue 3 (4th January 2021) - Medina‐Marino, Andrew; de Vos, Lindsey; Bezuidenhout, Dana; Denkinger, Claudia M.; Schumacher, Samuel G.; Shin, Sanghyuk S.; Stevens, Wendy; Theron, Grant; van der Walt, Martie; Daniels, Joseph
Abstract: Objective: The effectiveness of household contact investigations is limited by low referral uptake for clinic‐based TB testing by symptomatic household contacts. We qualitatively investigated the acceptability and perceived benefits of home‐based TB testing using a portable GeneXpert‐I instrument (GX‐I) in an urban South African township. Methods: In‐depth interviews were conducted with household contacts tested and those that observed testing. Semi‐structured interviews explored household contact's understanding of TB, perceptions of the GX‐I device and testing procedures, confidentiality, willingness to refer others, and views on home‐ vs . clinic‐based testing. Focus group discussions with home‐based TB testing implementing staff assessed operational considerations for scale‐up. Data were analysed using a constant comparison approach to qualitatively evaluate the acceptability and feasibility of home‐based TB testing. Results: Thirty in‐depth interviews and two focus group discussions were conducted. Observing one's own sputum being tested resulted in an emergent trust in home‐based TB testing, the GX‐I device and one's test results. Home‐based TB testing was considered convenient, helped to overcome apathy towards testing and mitigated barriers to clinic‐based testing. Perceptions that home‐based TB testing contributes to improved household and community health resulted in an emergent theme of alleviation of health insecurities. Operational concerns regarding inadvertent disclosure of one's diagnosis to household members and time spent in people's homes were identified. Conclusions: Home‐based TB testing was acceptable and feasible. Individuals expressed belief in the machine by being able to witness the testing process. Though most themes mirrored qualitative studies of home‐based HIV testing, the alleviation of health insecurities theme is unique to home‐based TB testing. Future research must evaluate the impact of home‐based TB testing on case finding yield, time‐to‐treatment initiation and household outcomes. Abstract : Objectif: L'efficacité des enquêtes sur les contacts familiaux est limitée par le faible taux de respect de l'orientation pour le dépistage de la tuberculose (TB) en clinique par les contacts familiaux symptomatiques. Nous avons investigué qualitativement l'acceptabilité et les avantages perçus du dépistage de la TB à domicile à l'aide d'un dispositif portable GeneXpert‐I (GX‐I) dans une ville urbaine sud‐africaine. Méthodes: Des entretiens approfondis ont été menés avec des contacts familiaux testés et ceux qui ont observé la pratique des tests. Des entretiens semi‐structurés ont permis d'explorer la compréhension de la TB par les contacts familiaux, les perceptions sur le dispositif GX‐I et les procédures de test, la confidentialité, la volonté de référer d'autres personnes et les opinions sur le dépistage à domicile ou en clinique. Des discussions de groupe focalisées avec le personnel chargé de la mise en œuvre du dépistage de la TB à domicile ont évalué les considérations opérationnelles pour le déploiement. Les données ont été analysées en utilisant une approche de comparaison constante pour évaluer qualitativement l'acceptabilité et la faisabilité du dépistage de la TB à domicile. Résultats: Trente entretiens approfondis et deux discussions de groupe ont été menés. L'observation de ses propres expectorations testées a conduit à une émergente de confiance dans le dépistage de la TB à domicile, le dispositif GX‐I et les résultats des tests. Le dépistage de la TB à domicile était considéré comme pratique, aidait à surmonter l'apathie envers le dépistage et atténuait les obstacles au dépistage en clinique. La perception selon laquelle le dépistage de la TB à domicile contribue à l'amélioration de la santé des ménages et de la communauté a donné lieu à l'émergence du thème de la réduction des insécurités sanitaires. Des préoccupations opérationnelles concernant la divulgation par inadvertance de son diagnostic aux membres du ménage et le temps passé au domicile des personnes ont été identifiées. Conclusion: Le dépistage de la TB à domicile était acceptable et faisable. Les individus ont exprimé leur croyance en la machine en étant en mesure d'assister au processus de test. Bien que la plupart des thèmes reflètent des études qualitatives sur le dépistage du VIH à domicile, le thème de l'atténuation des insécurités sanitaires est unique au dépistage de la TB à domicile. Les recherches futures doivent évaluer l'impact du dépistage de la TB à domicile sur le rendement de la recherche des cas, le délai de mise en route du traitement et les résultats au sein des ménages.